Occupational Hazards and Injuries Related to Veterinary Practices - Samadi, Assadullah (Journal of Natural Sciences – Kabul University, 2023)
Since its establishment, the veterinary profession has played a very valuable role in reducing health related problems caused by diseases and improving the living conditions of human societies. Veterinarians are a group of professionals who perform various medical services to diagnose, treat, control, prevent and eradicate animal diseases and zoonotic diseases, and they are the only doctors trained to protect the health of animals and humans. In general, veterinary medicine is considered one of the most dangerous professions, and veterinarians face various biological, chemical, physical and psychological hazards during veterinary practices and health services. To reduce such risks, it is necessary to make appropriate changes in the veterinary curriculum and the working environment of veterinarians, and to prepare and implement those rules that guarantee the health, social and economic conditions of veterinarians. Occupational hazards related to veterinary services and the ways to prevent them are discussed in this review article.